Dual regulation and redundant function of two eye-specific enhancers of the Drosophila retinal determination gene dachshund. - Pappu, K.S.; Ostrin, E.J.; Middlebrooks, B.W.; Sili, B.T.; Chen, R.; Atkins, M.R.; Gibbs, R.; Mardon, G. (Development, 2005)
Drosophila eye development is controlled by a conserved network of retinal determination (RD) genes. The RD genes encode nuclear proteins that form complexes and function in concert with extracellular signal-regulated transcription factors. Identification of the genomic regulatory elements that govern the eye-specific expression of the RD genes will allow us to better understand how spatial and temporal control of gene expression occurs during early eye development. We compared conserved non-coding sequences (CNCSs) between five Drosophilids along the approximately 40 kb genomic locus of the RD gene dachshund (dac). Our analysis uncovers two separate eye enhancers in intron eight and the 3' non-coding regions of the dac locus defined by clusters of highly conserved sequences. Loss- and gain-of-function analyses suggest that the 3' eye enhancer is synergistically activated by a combination of eya, so and dpp signaling, and only indirectly activated by ey, whereas the 5' eye enhancer is primarily regulated by ey, acting in concert with eya and so. Disrupting conserved So-binding sites in the 3' eye enhancer prevents reporter expression in vivo. Our results suggest that the two eye enhancers act redundantly and in concert with each other to integrate distinct upstream inputs and direct the eye-specific expression of dac.